Examining the Relationships Between Psychological Capital, Academic Performance, and Career Adaptability Among Medical Students in Saudi Arabia - Alqahtani, Elham; Alqahtani, Lama Abdullah (Journal of Posthumanism, 2026)
This study explored the relationships between psychological capital, academic performance, and entrepreneurial intentions among medical students in the Kingdom of Saudi Arabia using SmartPLS analysis. The research methodology employed in this study responses from 423 participants, including 254 males and 169 female medical students. The research established satisfactory to high levels of reliability for the constructs examined. Correlation analysis revealed significant positive associations among self-efficacy, hope, resilience, optimism, academic performance, and entrepreneurial intention. Self-efficacy emerged as a central factor, demonstrating strong correlations with hope, resilience, optimism, entrepreneurial intention, and academic performance. Direct effects analysis indicated that academic performance positively influences entrepreneurial intentions. Moreover, hope, optimism, resilience, and self-efficacy exhibited significant positive direct effects on both academic performance and entrepreneurial intentions. Mediation analysis highlighted the partial mediating role of academic performance in the relationship between psychological capital and entrepreneurial intentions. Total effects analysis confirmed the consistent influence of psychological capital on entrepreneurial intentions, with academic performance acting as a mediator. This study underscores the importance of psychological capital in shaping academic and entrepreneurial outcomes among medical students, providing insights for educators and policymakers aiming to support the development of future business leaders.